A knee brace alters patella position in patellofemoral osteoarthritis: a study using weight bearing magnetic resonance imaging. Issue 12 (December 2016) - Callaghan, M.J.; Guney, H.; Reeves, N.D.; Bailey, D.; Doslikova, K.; Maganaris, C.N.; Hodgson, R.; Felson, D.T.
Summary: Objective: To assess using weight bearing magnetic resonance imaging (MRIs), whether a patellar brace altered patellar position and alignment in patellofemoral joint (PFJ) osteoarthritis (OA). Design: Subjects age 40–70 years old with symptomatic and a radiographic Kellgren–Lawrence (K–L) evidence of PFJOA. Weight bearing knee MRIs with and without a patellar brace were obtained using an upright open 0.25 T scanner (G-Scan, Easote Biomedica, Italy). Five aspects of patellar position were measured: mediolateral alignment by the bisect offset index, angulation by patellar tilt, patellar height by patellar height ratio (patellar length/patellar tendon length), lateral patellofemoral (PF) contact area and finally a measurement of PF bony separation of the lateral patellar facet and the adjacent surface on the femoral trochlea (Fig. 1). Results: Thirty participants were recruited (mean age 57 SD 27.8; body mass index (BMI) 27.8 SD 4.2); 17 were females. Four patients had non-usable data. Main analysis used paired t tests comparing within subject patellar position with and without brace. For bisect offset index, patellar tilt and patellar height ratio there were no significant differences between the brace and no brace conditions. However, the brace increased lateral facet contact area ( P  = .04) and decreased lateral PF separation ( P  = .03). Conclusion: A patellar brace alters patellar position and increases contact area between the patella and femoral trochlea. These changes would lower contact stress at the PFJ. Such changes in patella position in weight bearing provide a possible biomechanical explanation for the success of the PFJ brace in clinical trials on PFJOA.